Effects of Risk Perception on Climate Change Special Events: A Focus on Value-Attitude-Behavior Model - Lee, Jong Yoon; Jun, Jong Woo (Indian Journal of Marketing, 2024)
Purpose : This study explored the consumer effect of climate change-themed public events. The value-attitude-behavior (VAB) model was used to model and validate the role of climate change risk perception. Methodology : An analysis of hierarchical regression was performed on the data gathered from the survey. The data analysis tool utilized was SPSS. Findings : As a result of the analysis, personal susceptibility and social susceptibility had a positive effect on the value of climate change-themed public events. Severity perception was also found to affect event value. Politically progressive orientation, social susceptibility, and severity perception were influencing event attitudes. It was found that political orientation and social susceptibility affected event participation behavior. Practical Implications: The study's findings have consequences for how attendees' perceptions of danger are accounted for in the VAB model for public events with a climate change theme. Moreover, event planning has practical ramifications since, for an event with a particular subject, how the theme is perceived is crucial. Originality : The current work, in contrast to other research on risk perception, constructs an extended VAB model that includes political orientation in addition to risk perception.
Keywords: Political Orientation; Risk Perception; Severity Perception; Value-Attitude-Behavior (VAB) Model; Climate Change Event